Lysyl oxidase-like 2 promotes esophageal squamous cell carcinoma cell migration independent of catalytic activity. (August 2020) - Zou, Haiying; Wen, Bing; Li, Run-Liu; Zhan, Xiu-Hui; Jiao, Ji-Wei; Liao, Lian-Di; Wu, Bing-Li; Xie, Wen-Ming; Xu, Li-Yan; Li, En-Min
Highlights: LOXL2-mediated ESCC cell migration is independent of amine oxidase activity. LOXL2 Y689F, LOXL2 ΔLO and LOXL2 ΔSRCR4, stimulate greater cellular migration than LOXL2 WT with no or low amine oxidase activity. LOXL2 ΔSRCR3 has low enzymatic activity and cellular migration ability compared with LOXL2 WT. Abstract: Lysyl oxidase-like 2 (LOXL2) is a member of the lysyl oxidase (LOX) family that contributes to tumor cell metastasis. Our previous data identified two splice variants of LOXL2 (i.e., LOXL2 Δ72 and Δ13) in esophageal squamous cell carcinoma (ESCC) cells that increased cell invasiveness and migration but had lower LOX activities than wild-type LOXL2 (LOXL2 WT). We generated a series of LOXL2 deletion mutants with different deleted biochemical domains and examined the relationship between the cell migration abilities and catalytic activities, as well as subcellular locations, of these deletion mutants compared with LOXL2 WT in ESCC cells to explore the mechanism of LOXL2-driven ESCC cell migration. Our results indicated that the deletion mutants of LOXL2 had impaired deamination enzymatic activity; LOXL2 ΔSRCR4, which lacks the fourth scavenger receptor cysteine-rich (SRCR) domain, had lower enzymatic activity; and LOXL2 Y689F had no catalytic activity compared with LOXL2 WT. However these two mutants stimulated greater cellular migration than LOXL2 WT. Furthermore, the degree of cell migration promoted by LOXL2 ΔLO (in which the LOX-like domain was deleted) was higher than that of LOXL2 WT, and LOXL2 ΔSRCR3, which does not have the third SRCR domain, had lower LOX activity and cellular migration ability than LOXL2 WT. These results suggested that LOXL2 promotes ESCC cell migration independent of catalytic activity.